2010
DOI: 10.1007/s00038-010-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic differences in the use of dairy fat in Russian and Finnish Karelia, 1994–2004

Abstract: The socio-economic differences in the use of dairy fat were stable in both areas but larger in North Karelia than in Pitkäranta. Our results support earlier assumptions of a weaker role of education as a determinant of health in Russia than in the western societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Mediterranean countries increased their consumption of meat, milk and sugar; meanwhile, some Northern countries decreased their intake of such foods and increased their fruit and vegetable consumption [21-26]. Dietary trends observed elsewhere in Central and Eastern European countries are similar to those found in Lithuania [10,11,27,28]. The increase in the availability of vegetable oils, margarines, fresh fruits and vegetables - even when out of season - was followed by rise in the consumption of healthier foods.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mediterranean countries increased their consumption of meat, milk and sugar; meanwhile, some Northern countries decreased their intake of such foods and increased their fruit and vegetable consumption [21-26]. Dietary trends observed elsewhere in Central and Eastern European countries are similar to those found in Lithuania [10,11,27,28]. The increase in the availability of vegetable oils, margarines, fresh fruits and vegetables - even when out of season - was followed by rise in the consumption of healthier foods.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have shown that people of higher socioeconomic status tend to have healthier diets than lower-status groups [7-9]. Social and economic changes in a country may impact nutrition habits, socio-demographic differences in diet, and other health behaviours of populations [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out among adults in Iran, Finland, Russia and the Baltic countries found an association between high educational level and frequent intake of fruits and vegetables [7,12,27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sociodemographic factors such as higher income, education, and age have been found to be associated with healthier dietary patterns in several other countries [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The sociodemographic variables were chosen on the basis of previous theoretical approaches (20,21) that have explained lifestyle changes in society. In addition, evidence obtained from studies on Finnish food consumption trends was taken into account (6,30) . Age was divided into 10-year groups.…”
Section: Predictor Variablesmentioning
confidence: 99%